Training of Future Heads of General Secondary Education Institutions in the Conditions of Educational Transformations - Iryna Darmanska (Pedagogical Discourse, 2023)
As a result of the implemented theoretical-methodological analysis, based on research in the field of philosophy, management, professional pedagogical education and own professional experience, it is proved that the formed managerial competence of the heads of institutions of general secondary education is the result of their readiness for practical managerial activity. The content of the phenomenon of «managerial competence» has been supplemented, which is interpreted as a set of knowledge, skills and abilities from the theory of organization of the institution of education, construction of the effective implementation of its structural units, management, legal aspects of the management of the educational institution, strategic and innovative management, management of educational and pedagogical activity, statutory activity, labour resources, content of internal school documentation, information communications, management techniques, audit and evaluation of managerial activity, psychological aspects of management, social and environmental safety of activity, use of educational technologies, as well as the availability of personal and professional qualities for their own self-realization, aimed at the desire for self-perfection, professional development and self- actualization, which the director of the school must thoroughly possess for the organization of both subject-subject relations, and for creating effective internal and external environment, application of managerial technologies, adoption of adequate managerial decisions.The pedagogical system of forming the managerial competence of the future heads of institutions of general secondary education in the process of continuous professional training has been worked out, which contributes to the qualitative realization of educational process and influences the effectiveness of the formation of managerial competency of undergraduates and represents a set of elements of the macro and micro environment of a higher education institution, united by a unified purpose, interconnectedness, aimed at achieving the desired result.